2022
DOI: 10.1111/ijfs.15720
|View full text |Cite
|
Sign up to set email alerts
|

Distilled grape pomace as a functional ingredient in vegan muffins: effect on physicochemical, nutritional, rheological and sensory aspects

Abstract: Wheat-based vegan muffins were formulated with increasing levels (0, 5 and 10 g per 100 g substitutes to flour) of dried grape pomace powder obtained after distillation (DGPP). The DGPP-muffins showed a greater (P < 0.05) total dietary fibre and a lower (P < 0.05) total starch content to the control. The inclusion of DGPP influenced (P < 0.05) both the batter's rheological properties and the baked muffins' technological characteristics, including the baking loss, the volume, the firmness, the spread ratio and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…with the addition of blueberry dried pomace (up to 30%) and sweet corn cob flour (up to 20%), respectively. Contrary, Bianchi et al 8 . reported firmness increase when grape pomace powder (DF content 55.6%) was incorporated to the muffin formulation in 5% or 10%.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…with the addition of blueberry dried pomace (up to 30%) and sweet corn cob flour (up to 20%), respectively. Contrary, Bianchi et al 8 . reported firmness increase when grape pomace powder (DF content 55.6%) was incorporated to the muffin formulation in 5% or 10%.…”
Section: Resultsmentioning
confidence: 92%
“…who found that the addition of different percentages of seed powder and Guava pomace to the mixture for cupcakes allowed to obtain values between 2.22 and 1.42 cm 3 g −1 . Bianchi et al ., 8 reported SV of 1.39 and 1.09 cm 3 g −1 for vegan muffins obtained using 5% and 10% flour replacement by dried grape pomace powder, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations